THE IMPORTANCE-PERFORMANCE ANALYSIS OF COMPENSATION PROGRAMS AT PT. BANK RAKYAT INDONESIA TONDANO, MINAHASA - Paat, vabiola R; Tumbuan, Willem J. F. A.; Rumokoy, Farlane S (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract:Employee will give high levels of performance for the company if they are appreciated and compensating accordingly. This research is descriptive research using Importance-Performance Analysis as the analytical tool. The objective is to analyze the importance and performance of compensation programs at PT. Bank Rakyat Indonesia Tondano, Minahasa with the total respondent is 33 and 8 total variables. The result of the research shows that Job Grade and Incentive are in the Quadrant II; Salary, Annual Leave, Religious Holiday Allowance, and Hospital Care Coverage are in Quadrant I; following by Premium Allowance and Overtime Pay are in Quadrant III. Thus, the company need to execute more about the compensation that have high importance but have low performance.Keywords: compensation, importance performance analysis, PT. Bank Rakyat Indonesia